2016
DOI: 10.31018/jans.v8i3.971
|View full text |Cite
|
Sign up to set email alerts
|

Partial acidulation of phosphate rock for enhanced phosphorus availability in alluvial soils of Bihar, India

Abstract: The present study was undertaken to fractionate partially acidulated phosphate rock (PAPR) and evaluate its effect on Phosphorus availability in alluvial soils. For this purpose, low grade phosphate rock was collected from Udaipur, Rajasthan and acidulated at different degrees with sulphuric acid (H2SO4) (v/v)Results from an incubation study showed that the available fraction of P [Water soluble (WSP) and Citrate soluble (CSP)] increased with increasing degree of acidulation. The maximum WSP was obtained at 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Otherwise, additives PILC and zeolite do not seem to be effective in increasing P agronomic efficiency (Table 5). Numerous published research studies on the effectiveness of partially acidulated phosphate fertilizers found conflicting results [57,[61][62][63][64][65][66]. This is attributed to differences in the physical form of application (powder versus granular), the products used for acidulation, the type of soil used to test the fertilizers and the doses tested [57,67].…”
Section: Agronomic Efficiencymentioning
confidence: 99%
“…Otherwise, additives PILC and zeolite do not seem to be effective in increasing P agronomic efficiency (Table 5). Numerous published research studies on the effectiveness of partially acidulated phosphate fertilizers found conflicting results [57,[61][62][63][64][65][66]. This is attributed to differences in the physical form of application (powder versus granular), the products used for acidulation, the type of soil used to test the fertilizers and the doses tested [57,67].…”
Section: Agronomic Efficiencymentioning
confidence: 99%